Determining the marketing capabilities of small and medium-sized industries for the international market - Salari Sharif, Pooya; Salehi, Sepehr; Forghani, Hadi (Revista Publicando, 2018)
Today, competition in the current conditions of the export market, forces the organizations to adopt strategies to confront this competition in order to achieve higher export performance, but achieving higher performance is something that some researchers consider as the result of paying head to and this has become more important in manufacturing and service organizations.The research method is descriptive survey. The data collection method is in two sections: library and field studies. Given the fact that the size of the statistical society of the industries of automobile industrial park of Bam Special Economic Zone is 1606, the sample size of the desired Morgan table should be at least 210. To analyze the data, Excel software for data recording and data analysis, and SPSS and AMOS statistical software were used to test the hypotheses of the research. The results show that internet marketing capability has a direct and significant effect on access to information, access to information has a direct and significant effect on the international strategy, internet marketing capability has a direct and significant effect on the international pivotal strategy, the international pivotal strategy has a direct and significant effect on the international business, internet marketing capability has a direct and significant effect on the international network capability, the international strategy has a direct and significant effect on the international network capability, the ability of the international network have a direct and significant impact on international business in Bam automotive companies in special economic zone there. Therefore, it is suggested that managers should create structures, processes and new methods for doing business and develop an export strategy in all sectors and enhancing interact among the marketing capabilities and developing the international market, in order to create the value of the market of exporters industries.